Promoting Transdisciplinarity and Competency-based Learning Using Web GIS in the Spanish Secondary School Classroom - Puertas-Aguilar, Miguel-Ángel; Álvarez-Otero, Javier; de Lázaro-Torres, María-Luisa (European Journal of Geography, 2025)
In today´s world, education systems must adapt to stay connected with the real world. Three key elements meet these demands: the interaction between disciplines and their varying levels of complexity, the competency-based approach of the Spanish education system, and the use of web-based GIS tools for teaching and learning with a transdisciplinary approach. In this context, Spain offers a promising context to explore the integration of these elements, given its educational reforms and digital strategy. However, there are no studies in secondary schools in Spain integrating these elements. The objective of this research is to demonstrate that web GIS serves as a valuable resource for engagement in the real world, representing information on maps for teaching and learning within a transdisciplinary competency-based framework. The methodology applied follows the action-research model mainly based on classroom observations and students’ satisfaction surveys. Several stages have been considered: a) planning: identifying a relevant problem or topic to improve learning outcomes; b) action: class intervention by collecting necessary information, categorizing information, analysing the problem, formulating hypotheses and creating a layer for a collaborative map; c) results and interventions assessments. Following this methodology, three interventions are presented. The sample is a convenience sample with 187 students aged 15 to 18 (ISCED 3: 4th-year Compulsory Secondary Education -K-10, ages 15–16- and ISCED 4: 2nd-year Baccalaureate -K-12, ages 17–18-), from a Spanish educational institution. It can be stated that the collaborative use of web-based GIS in secondary education enhances engagement, representation of information, and increases interaction. All these actions improve sustainability, digital, learning to learn and citizenship competencies and promote transdisciplinarity. Highlights: Collaborative use of web GIS improves the engagement of students in Secondary School. Cartography based on the use of web GIS drives the transdisciplinary approach. Interventions evaluate sustainability, digital, learn to learn and citizenship competencies.